Government Reporting and Quality of Public Services: Are They Twins? - Puspa Kusuma Pertiwi; Puji Wibowo (Journal of Accounting and Investment, 2023)
Research aims: This study aims to analyze the effect of audit findings and audit recommendation follow-up on the quality of public services through the quality of financial reports.Design/Methodology/Approach: This study employed cross-sectional regression using data from 170 observations of 34 ministries and institutions in Indonesia for the 2015-2019 period by adopting a purposive sampling method. Hypotheses testing was performed using binary logistic regression analysis, multiple linear regression, and path analysis.Research findings: The results showcased that the audit findings negatively impacted the quality of financial reports, while audit recommendation follow-up did not affect the quality of financial reports. The audit findings also did not influence the quality of public services, while audit recommendation follow-up led to better public services.Practical and Theoretical contribution/Originality: Central government institutions are expected to improve the effectiveness of the internal control system and compliance with laws and regulations in managing state finances to create more quality and reliable financial information. These institutions are also encouraged to overcome non-tax revenue irregularities to promote good governance in public service. The study provides empirical evidence regarding the determinants of public service quality by developing new measurements associated with the characteristic of non-tax revenue imposed by the line ministries and agencies.Research limitation: Future research is needed to develop the quality of public service indicators with other indicators and consider using primary data through a questionnaire survey to measure the quality of public services.